2010
DOI: 10.1523/jneurosci.3289-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Src Homology 2 Domain Protein Shep1 Plays an Important Role in the Penetration of Olfactory Sensory Axons into the Forebrain

Abstract: Shep1 is a multidomain signaling protein that forms a complex with Cas, a key scaffolding component of integrin signaling pathways, to promote the migration of non-neuronal cells. However, the physiological function of Shep1 in the nervous system remains unknown. Interestingly, we found that Shep1 and Cas are both concentrated in the axons of developing olfactory sensory neurons (OSNs). These neurons extend their axons from the olfactory epithelium to the olfactory bulb located at the anterior tip of the foreb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…However, deficiencies in Shep1-Cas function may result in defects in axon growth or dendritic spine morphology [38, 39, 44], abnormalities that may only be revealed by a more detailed analysis. Indeed, in other studies we found that the axons of developing olfactory sensory neurons fail to connect to their synaptic targets in the olfactory bulb in Shep1 knockout mice [23]. We also detected morphological abnormalities in the dendritic spines of hippocampal pyramidal neurons of adult Shep1 knockout mice (Wang and Pasquale, unpublished data).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…However, deficiencies in Shep1-Cas function may result in defects in axon growth or dendritic spine morphology [38, 39, 44], abnormalities that may only be revealed by a more detailed analysis. Indeed, in other studies we found that the axons of developing olfactory sensory neurons fail to connect to their synaptic targets in the olfactory bulb in Shep1 knockout mice [23]. We also detected morphological abnormalities in the dendritic spines of hippocampal pyramidal neurons of adult Shep1 knockout mice (Wang and Pasquale, unpublished data).…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, the Shep1ΔN fragments are not sufficient to promote Src activity and Cas phosphorylation, highlighting the importance of the SH2 domain in the physiological function of Shep1. Consistent with a functional deficiency of Shep1ΔN, we found that a Shep1 fragment similar to those expressed in the knockout mice does not promote cell invasion through collagen in Transwell assays when ectopically expressed in HEK 293 cells [23]. Similarly, a truncated form of BCAR3/AND-34 without the N-terminus and the SH2 domain has also been recently reported to be functionally deficient in breast cancer cells [17].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, the corresponding domain on Chat-H appears to lack enzymatic activity 14 . Chat-H and Chat are identical except for a unique N-terminal 180 amino acid sequence that is present on Chat-H. Chat-H was cloned as a protein that positively regulated TCR signaling and IL-2 production in T cells 15 , whereas Chat was shown to mediate penetration of olfactory sensory axons into the forebrain 16 .…”
Section: Introductionmentioning
confidence: 99%